EFFECT OF CAPABILITY AND AUTHORITY ON INTELLECTUAL CAPITAL EMPLOYEES AT PKS PTPN V SEI PAGAR - Zamhir Basem; Mega Ariati; Yulizar Yulizar (STIE Bangkinang Publishing, 2022)
This research aims to identify the effect of capability and authority on the intellectual capital of employees at PKS PT. Nusantara Plantation VSei Fence. Intellectual Capital is a feature needed to find opportunities and manage threats in life. The analysis used in this research is a multiple linear analysis with a total of 121 respondents. Hypothesis testing was tried with the F test and t test. Based on the research results, it can be concluded that simultaneously and partially capability and authority affect the intellectual capital of employees. The closeness of the bond between the independent variable and the dependent variable is strong with the donation of the independent variable to the dependent variable of 68.0%, while the remaining 32.0% is determined by other variables not listed in this research.